Performance Indicator for Public Expenditure Efficiency in Thai Basic Education: Data Envelopment Analysis Approach for the Future Improvement - Kedcham, Akadet (Scholar: Human Sciences, 2014)
The purposes of this paper are 1) to develop a model to measure the performance of public expenditure in Thai basic education 2) to identify the association between efficiency score and school size by using Pearson moment correlation. The data for the study were obtained from following sources. The National Institute of Educational Testing Service (NIETS) and the office for National Education Standards and Quality Assessment (ONESQA) over the period 2007-2008. To identify the best performance schools, The Data Envelopment Analysis (DEA) methodology enables to aggregate performance indicators in order to obtain a public expenditure efficiency measure through the comparison of 164 Thai basic education schools. Moreover, the second stage Pearson product moment correlation was used to assess whether there is a relationship between efficiency score and school size. The research findings were summarized as follows: The average efficiency of these schools is 0.706 (primary school) and 0.713 (secondary school) which is quite high. However, efficiency scores of individual schools range from 0.191 to 1, which shows that some schools are significantly less productive. The correlation analysis found the significant positive relationship between school size and efficiency score at 5% significance level.